Suffering at the Margins: Applying Disability Critical Race Studies to Trafficking in the United States - Rein, Rachel (Columbia Journal of Gender and Law, 2022)
Human trafficking is a scourge in which perpetrators victimize the most vulnerable and marginalized members of a population to sell their bodies or sell their labor for profit. This Note explores human trafficking in the United States through Disability Critical Race Studies (DisCrit). First, the Note offers background on trafficking and applicable federal law. Not only does trafficking disable people, but people with preexisting disabilities are especially at risk for trafficking. Next, the Note shows that trafficking law follows a law-and-order framework: a framework that prioritizes prosecuting traffickers and doles out penal remedies. This framework and its intimate ties with the criminal justice system is a dual-edged sword. It helps countless survivors yet retraumatizes some marginalized survivors. Finally, the Note introduces DisCrit, justifies its use for anti-trafficking advocacy, and applies the DisCrit framework. By looking at trafficking law through DisCrit, one sees that trafficking law must work with—not against—survivors to end human suffering.